(untitled) (Research, Society and Development, 2020)
The search for suitable materials for functional covering layers on landfills is a great challenge, especially for cities situated in arid regions. The use of conventional cover layers in arid regions is nearly impossible, due to drying of soil and opening of fissures which allow infiltration of external agents harmful to the landfill. Thus, the aim of this study is to evaluate the strength of the mixture of a clay soil used in sanitary landfills with organic compound for use in covering layers. Triaxial and direct shear strength tests were performed according to the ASTM standards D4767 and D3080, respectively, to determine the mechanical strength of the mixtures. The tests were performed on pure clay soil and mixtures with proportions of 2:1 and 1:1 (soil:compound) for comparison. Test results showed the addition of organic compound does not expressively reduce the mechanical strength of the soil, guaranteeing their use without loss to the stability and geotechnical safety of the location.